The Plasma Membrane-Localized Sucrose Transporter IbSWEET10 Contributes to the Resistance of Sweet Potato to Fusarium oxysporum - Li, Yan; Wang, Yannan; Zhang, Huan; Zhang, Qian; Zhai, Hong; Liu, Qingchang; He, Shaozhen (Frontiers in Plant Science, 2017)
SWEET (Sugars Will Eventually be Exported Transporter) proteins, a novel family of sugar transporters, mediate the diffusion of sugars across cell membranes and acts as key players in sucrose phloem loading. Manipulation of SWEET genes in plants leads to various effects on resistance to biotic and abiotic stresses due to disruption of sugar efflux and changes in sugar distribution. In this study, a member of the SWEET gene family, IbSWEET10, was cloned from the sweet potato line ND98. mRNA expression analysis in sweet potato and promoter GUS analysis in Arabidopsis showed that IbSWEET10 is highly expressed in leaves, especially in vascular tissue. Transient expression in tobacco epidermal cells revealed plasma membrane localization of IbSWEET10, and heterologous expression assays in yeast indicated that IbSWEET10 encodes a sucrose transporter. The expression level of IbSWEET10 was significantly up-regulated in sweet potato infected with Fusarium oxysporum Schlecht. f. sp. batatas. Further characterisation revealed IbSWEET10-overexpressing sweet potato lines to be more resistant to F. oxysporum, exhibiting better growth after infection compared with the control; conversely, RNAi lines showed the opposite results. Additionally, the sugar content of IbSWEET10-overexpression sweet potato was significantly reduced, whereas that in RNAi plants was significantly increased compared with the control. Therefore, we suggest that the reduction in sugar content caused by IbSWEET10 overexpression is the major reason for the enhanced F. oxysporum resistance of the transgenic plants. This is the first report that the IbSWEET10 transporter contributes to the resistance of sweet potato to F. oxysporum. The IbSWEET10 gene has the great potential to be used for improving the resistance to F. oxysporum in sweet potato and other plants.